Improve the interfacial properties of carbon fiber reinforced epoxy resin composites by maleimide‐modified waterborne polyurethane sizing agent. Issue 11 (20th January 2023) - Li, Chengsen; Gao, Xueping; Zhu, Bo; Yuan, Xiaomin; Qiu, Zhijie; Zhang, Ye; Yan, Shuhan
Abstract: The N‐(4‐hydroxyphenyl) maleimide (4‐HPM) modified waterborne polyurethane emulsions (MWPU) were used as surface sizing agents to improve the interfacial adhesion between carbon fibers (CF) and epoxy resin matrix. Dynamic light scattering (DLS), transmission electron microscope (TEM), and thermogravimetric analysis (TGA) showed the particle size distribution, storage stability, and thermal stability of the modified MWPU. And the surface reactivity of CF increased significantly after sizing. The interfacial shear strength (IFSS) and the interlaminar shear strength (ILSS) of CFREs were tested, and the fracture morphology was observed. The result showed that a continuous and uniform sizing layer is formed on the surface of CF. In particular, the comprehensive performance and interfacial modification effect of the MWPU emulsion outperformed other samples when the 4‐HPM content was 1.0 wt%. Compared with unsized carbon fibers, the IFSS and ILSS are up to 71.30% and 30.81% higher, respectively. Abstract : The IFSS of CF and ILSS of CFREs before and after sizing. Typical fracture morphologies of carbon fiber surfaces after interfacial debonding: (a0 ) UCF, (a) SCF‐1, (b) SCF‐2, (c) SCF‐3, and (d) SCF‐4.